PENGEMBANGAN TEORI KEYNESS DALAM JUMLAH KONSUMSI MUSLIM - Muhammad Reza Hermanto (Signifikan: Jurnal Ilmu Ekonomi, 2015)
The objective of this research is to implement the tought of John Maynard Keynes about consumer behavior and also its antithesis. This study takes muslim as a research subject because Islam as a religion own an institution in order to regulate every muslim in doing consume. This research was expected to find out whether  the  development  of  Keynes’s  theory  (thesis  and  antithesis)  could  be implemented in muslim community or not. The variables which used in the model are ammount of consumption (Y), income rate (X1), age (X2), religiosity (X3), and distinguishing community (faculty) as a dummy. Through multiple regression with dummy variable method, from 60 muslim respondents in two different community, was  found  that  income  rate  (X1)  and  age  (X2)  was  effected  positively  and significant to ammount of consumption (Y), religiosity (X3) was effected negatively and significant to ammount of consumption (Y), while dummy variable which  is distinguishing community (faculty) was not effected significantly to ammount of consumption  (Y).  Therefore  the  dummy  variable  has  dropped  out  from  the research model.DOI: 10.15408/sjie.v4i2.2304